Orbital alveolar soft part sarcoma: clinicopathological characteristics and prognostic prediction - Te Zhang; Keyun Xue; Huijing Ye; Wei Xiao; Huasheng Yang (BMC Ophthalmology)
Abstract Objective To explore the clinicopathological characteristics and prognosis of orbital alveolar soft part sarcoma (ASPS), providing a basis for its diagnosis and treatment. Methods Patients diagnosed with primary orbital ASPS at the Zhongshan Ophthalmic Center of Sun Yat-sen University from 2014 to 2024 were included. A retrospective analysis of clinical data, imaging findings, pathological features, immunohistochemistry results, etc., was conducted. Follow-up data were also analyzed. Results A total of 7 patients (7 eyes) were included in the study, consisting of 4 males and 3 females, aged between 2 and 47 years (median age 27 years), with follow-up period range from 16 to 201 months. Orbital protrusion was the most common presenting symptom (5/7), with one case involving invasion of the paranasal sinuses. During follow-up, all patients survived, and two patients experienced recurrence, all localized to the orbit. Recurrence was more common in younger patients, with an average recurrence time of 10 months post-surgery. High Ki67 expression was significantly associated with local recurrence (P = 0.047). Conclusion Primary orbital ASPS generally exhibits indolent biological behavior, and complete surgical excision can lead to long-term control. However, patients with high Ki67 expression should be closely monitored due to the higher risk of recurrence.